EFFECTIVE TEACHING BECOME A DETERMINER OF THE QUALITY OF A TEACHER - Nagata Zamzami (EZRA SCIENCE BULLETIN, 2023)
The educational process in schools is faced with the complexity and variety of student behavior in the learning process, the success of students in the learning environment even though it is influenced by the innate nature of individual students and their environment, but the teacher's role in learning becomes the most dominant focus of hope for student success in learning expected by all parties. Of course, based on these expectations, effective teaching skills in all respects are needed. Teachers must have knowledge of teaching materials from various perspectives, expertise in how to teach it, be professional in carrying out their teacher's duties, commitment and high motivation to pay attention to their students.